2016
DOI: 10.19154/njwls.v6i2.4967
|View full text |Cite
|
Sign up to set email alerts
|

Why do Third Sector Employees Intend to Remain or Leave their Workplace?

Abstract: Third sector employees have claimed to enjoy high job satisfaction and low turnover intentions because their work is considered intrinsically rewarding. Employees have strong motivation for public service and they consider the organization’s goals as their own. This makes work meaningful and thus reduces turnover intentions. Changes in the third sector institutional environment, however, have intensified the working environment. This probably undermines job quality and thus increases turnover intentions. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 1. Existing research also suggest that nonprofit employees and volunteers are also driven by egoistic motives (Mesch, Tschirhart, Perry, & Lee, 1998; Selander & Ruuskanen, 2016; Veludo-de-Oliveira, Pallister, & Foxall, 2015). …”
mentioning
confidence: 99%
“… 1. Existing research also suggest that nonprofit employees and volunteers are also driven by egoistic motives (Mesch, Tschirhart, Perry, & Lee, 1998; Selander & Ruuskanen, 2016; Veludo-de-Oliveira, Pallister, & Foxall, 2015). …”
mentioning
confidence: 99%
“…The role of third sector actors has mainly been discussed in regard to WISE and cross-sector partnerships in social innovation studies (Leca et al 2019;Oeij et al 2018) and in regard to professionalization and organizational management in civil society studies (Hvenmark 2013(Hvenmark , 2016. It is concluded that TSOs are increasingly run by paid employees rather than unpaid volunteers, despite their long tradition of combining employment and volunteering in their operations (Jutterström et al 2018;Selander & Ruuskanen 2016). Surveys reveal that employees in Swedish TSOs find their work to be more meaningful, free, and flexible than in the private or public sector, while the working conditions, wage levels, and career opportunities are considered to be poorer (Jutterström et al 2018;Unionen 2016).…”
Section: Innovative Work Inclusionmentioning
confidence: 99%